PEDAGOGICAL FOUNDATIONS OF USING NATIONAL HERITAGE IN EDUCATION OF SPIRITUAL AND MORAL QUALITIES OF PRIMARY SCHOOL STUDENTS - Sattarova Munojaot Tokhtayevna; S. I. Tursunova (American Journals, 2023)
In this article, problems related to the use of our national heritage in education of spiritual and moral qualities of primary school students, development of creative criteria for the development of the culture of use of our national heritage.
Keywords: primary school students, education of spiritual and moral qualities, our national heritage, spiritual values, independent education.